Anaerobic power and muscle strength characteristics of 11 years old elite and non-elite boys and girls from gymnastics, team handball, tennis and swimming - Bencke, J.; Damsgaard, R.; Saekmose, A.; Jorgensen, P.; Jorgensen, K.; Klausen, K. (Scandinavian Journal of Medicine & Science in Sports, 2002)
The aim of the present investigation was to study the possible effects of specificity of training on muscle strength and anaerobic power in children from different sports and at different performance levels in relation to growth and maturation status. Hundred and eighty-four children of both gender participating either in swimming, tennis, team handball or gymnastics were recruited from the best clubs in Denmark. Within each sport, the coach had divided the children into an elite (E) and non-elite (NE) group according to performance level and talent. Tanner stage assessment and body weight and height measurements were performed by a physician. The anaerobic performances were assessed by Wingate tests and jumping performance in squat jump (SJ), countermovement jump (CMJ) and drop jump (DJ) from two heights. Most of the differences between groups in Wingate performance disappeared when the data were normalised to body mass. The gymnasts were the best jumpers and their superiority were increased in the more complex motor coordination tasks like DJ. The results may indicate some influence of training specificity, especially on the more complex motor tasks as DJ and there may be an effect of training before puberty. The performance in the less complex motor tasks like cycling and SJ and CMJ may also be influenced by specific training, but not to the same extent, and heritance may be an important factor for performance in these anaerobic tasks.